Sentences with the Construction for + n/pr + infinitive and Complex Sentences as Syntactical Synonyms in Modern English - Лeвинене А. (Kalbotyra, 1973)
Sentences with the construction for + n/pr + infinitive and complex sentences are treated as syntactical synonyms in Modern English. The choise of a synonymous construction depends upon the following conditions: 1) semantics of the word introducing the construction; 2) general syntactical structure of the sentence; 3) stylistic peculiarities of the sentence (or the context).